Estudo das alterações no volume muscular, na função articular e na marcha de hemiparéticos crônicos - Medeiros, Christiane Lanatovitz Prado (Universidade Federal de São Carlos, 2010)
This work consists of two studies. The aim of the first study was to investigate quadriceps and hamstring muscle volumes and strength deficits of the knee extensors and flexors in people with chronic hemiparesis compared to a healthy group. Fifteen individuals with chronic stroke and fifteen healthy individuals took part in this study. Motor function, quadriceps and hamstring muscle volume (MV), and maximal concentric and eccentric contractions of the knee extensors and flexors were obtained. The quadriceps muscle showed a reduction in MV. The peak torque of the paretic and non paretic limbs knee extensors and flexors was reduced in both contraction modes and velocities. There were significant correlations between motor function and strength deficits. With regard to muscle mass, there was a difference between quadriceps and hamstring response. There was no disuse atrophy; however this did not prevent extensor torque reduction. The aim of the second study was to investigate the effects of ground level gait training combining body weight support (BWS) and functional electrical stimulation (FES). Twelve people following chronic stroke. An A1-B-A2 system was applied; A1 and A2 corresponded to ground level gait training using BWS, and B corresponded to the same training associated to FES. The analyzed variables were: mean walking speed of locomotion; step length; stride length, speed and duration; initial and final double support duration; single-limb support duration; swing period; range of motion (ROM), maximum and minimum angles of foot, leg, thigh, and trunk segments. Mean walking speed, stride length and speed increased. Regarding the ROMs, there was a significant increase for leg and thigh. There was not improvement in the variables measured during the FES phase. Ground level gait training using BWS was effective to improve some gait, and the association to FES did not provide any additional improvement in the measured parameters.
Keywords: Fisioterapia; Hemiparesia; Cinemática; Avaliação isocinética; Torque; Intervenção; Acidente Vascular Encefálico; Volume muscular; Força muscular; Dinamômetro isocinético; Parâmetros espaço-temporais; Ângulos segmentares; Stroke; Muscle volume; Muscle strength; Isokinetic dynamometer; Intervention; Spatial-temporal parameters; Segmental angles; Kinematics; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL